Pengembangan Bahan Ajar Multimedia Berbasis Flipbook Materi Teknik Half Volley Forehand dan Backhand Pada Mata Kuliah TP. Pembelajaran Tenis Lapangan: Development of Flipbook-Based Multimedia Teaching Materials for Half Volley Forehand and Backhand Techniques in the Tennis Course - Sang Ayu Putu Oktamayani; Peby Gunarto; Ni Luh Putu Spyanawati (Jurnal IKA, 2026)
This research is research and development orR&D (Research and Development). The research method used in this study is the ADDIE Model which focuses on product development in the form of multimedia-based teaching materialsflipbookon engineering materialshalf volley forehand And backhandin the TP course. Tennis Learning. The research subjects were physical education students at Ganesha University of Education. Data collection was classified into two types: qualitative and quantitative data. through the stages of observation and questionnaire distribution. The results of the research on the validity test were obtained from the content or learning material expert test at 98%, then from the field practitioner expert test at 97%. The learning media content expert at 100% and the design expert at 97%. Furthermore, the percentage results from the individual trial showed a value of 98%, then the small group trial showed a value of 97%. and the results of large group trials, the overall percentage obtained was 96%. Thus, the product or media of digital teaching materials based onflipbookThe developed materials were declared highly suitable for use by students. These results indicate that the teaching materials are able to support understanding of the material effectively and interactively.